Optimizing ploy (ε-caprolactone) scaffolds for mouse embryonic stem cells. - Wong, Cher Hao. (2010)
This project main motivation is to optimize the electrospinning of PCL scaffolds for mES cells study. 3 solvents were employed to dissolve the PCL: TFE, TFE with PBS and chloroform/methanol. The optimization involves tweaking parameters like, polymer concentration, solution conductivity, solution flowrate, needle tip to collector distance and applied voltage to alter spun fiber mat for uniformity in the fiber diameter. The project was split into 3 major stages: 1. Optimization of random fiber scaffolds. 2. Optimization of aligned fiber scaffolds. 3. mES cells studies on PCL scaffolds. Optimization was done to obtain parameters used for electrospinning usable scaffolds in each stage. These parameters were then translated to reference point for electrospinning fibers at the next stage. During the PCL in TFE optimization stage, it was found that lower PCL concentration solution will spin a scaffold with thinner fiber diameter. And during the PCL in TFE with PBS optimization stage, the addition of PBS thins the polymer jet and thus reducing the scaffolds fiber diameter as compared to PCL in TFE scaffolds. PBS also caused the thinning and splitting of the fiber jet during the spinning process, which caused web-like structures to form in 8 of the scaffolds, and also 3 scaffolds to be unusable.